Boceprevir in liver transplant recipients. (11th April 2014) - Saab, Sammy; Manne, Vignan; Bau, Sherona; Reynolds, Justin A.; Allen, Ruby; Goldstein, Leonard; Durazo, Francisco; El‐Kabany, Mohammed; Han, Steven; Busuttil, Ronald W.
Abstract Background There has been increasing interest in using protease inhibitors with pegylated interferon and ribavirin to treat recurrent hepatitis C (HCV) disease in liver transplant recipients. Methods We retrospectively evaluated the safety and efficacy in liver transplant recipients treated for recurrent hepatitis C genotype 1 with the combination of peginterferon, ribavirin and boceprevir. Results Twenty liver transplant recipients were treated for recurrent hepatitis C. Baseline alanine aminotransferase, total bilirubin and HCV RNA values (± SD) were 67.5 (±50.9) mg/dl, 1.78 (±1.99) U/L, and 16 955 510 (±21 620 675) IU/ml. Anaemia was a common adverse event requiring epoetin in 16 of 20 recipients and ribavirin dose reductions in 17 of 20 recipients. One‐third of recipients required a blood transfusion. Filgrastim was used in 11 of 20 patients (55%) and eltrombopag in two of 20 recipients (10%) over the course of treatment. Serum creatinine level increased significantly from a baseline value of 1.33 mg/dl to 1.59 mg/dl at week 20 of boceprevir (P < 0.005). The overall sustained viral response (SVR) was 50%. Of the 14 patients who had a viral load less than 1000 IU/ml at week 4 of boceprevir, the SVR was 71%. The SVR was 83% of the 11 patients who had undetectable viral levels at week 4 of boceprevir. Conclusions Antiviral therapy utilizing boceprevir in liver transplant recipients requires close monitoring. Anaemia and neutropenia were common requiring growth factors in most recipients. On‐treatment viral responses appear promising but long‐term data are needed.